Arterial structure and function in Africans with HIV for > 5 years: longitudinal relationship with endothelial activation and cardiovascular risk markers. Issue 8 (5th May 2021) - Phalane, E; Fourie, CMT; Schutte, AE; Kruger, IM; Mels, CMC
Abstract : Objectives: We aimed to determine whether people with human immunodeficiency virus (PWHIV) have increased measures of arterial injury [carotid intima‐media thickness (cIMT)] and large artery stiffness [carotid‐femoral pulse wave velocity (cfPWV)] when compared with their counterparts without HIV, and whether baseline markers of endothelial activation and cardiovascular risk are associated with cIMT and cfPWV after 5 years. Methods: We matched 126 PWHIV from North West Province, South Africa, to 126 without HIV according to age, sex and locality. Cardiovascular risk and endothelial function markers [soluble intracellular adhesion molecule (ICAM‐1) and soluble vascular cell adhesion molecule (VCAM‐1)] were measured at baseline and cIMT and cfPWV at follow‐up. Results: This study included 21.4% men. The use of antiretroviral therapy (ART) increased from 44.1% at baseline to 81.4% at follow‐up. At follow‐up, cIMT ( P = 0.90) and cfPWV ( P = 0.35) were similar in the groups. Despite elevated ICAM‐1 and VCAM‐1 in the PWHIV (all P < 0.001) at baseline, these markers did not associate with cIMT and cfPWV after 5 years. In multivariable‐adjusted regression analysis, cIMT associated positively with age ( β = 0.31, P = 0.002) and triglyceride: high‐density lipoprotein‐cholesterol ( β = 0.23, P = 0.016) in PWHIV. Mean arterial pressure (MAP) ( β = 0.28, P = 0.010) associated positively with cfPWV in the PWHIV. In the people without HIV, sex ( β = 0.31, P = 0.004) and glycated haemoglobin (HbA1c) ( β = 0.24, P = 0.026) associated with cIMT while age ( β = 0.17, P = 0.049), sex ( β = 0.29, P = 0.003), MAP ( β = 0.31, P = 0.001) and HbA1c ( β = 0.21, P = 0.041) associated positively with cfPWV. Conclusions: Measures of arterial structure and function were similar in Africans with HIV and their age, sex and locality matched controls. Traditional cardiovascular risk markers rather than elevated endothelial activation at baseline were independently associated with cIMT and cfPWV over 5 years.